CRYPTOCURRENCY MARKET CYCLES - Oleksii Dotsenko (Соціальна економіка)
This article is dedicated to a detailed analysis of market cycles in cryptocurrencies and their impact on investment strategies. The article thoroughly examines various stages of these cycles, their characteristics, and their interconnections with other economic factors. It explores the factors influencing the duration and intensity of these cycles, as well as methods of utilizing them to develop successful investment strategies. The research findings highlight the importance of understanding psychological factors such as FOMO (fear of missing out) and FUD (fear, uncertainty, and doubt), as well as the impact of halving on the cryptocurrency market. Investors who comprehend these aspects and adapt their strategies to the volatile market conditions can achieve success in their investments.